2012
DOI: 10.1302/0301-620x.94b4.27772
|View full text |Cite
|
Sign up to set email alerts
|

The World Health Organization ‘5 Moments of Hand Hygiene’

Abstract: The World Health Organization (WHO) launched the first Global Patient Safety Challenge in 2005 and introduced the ‘5 moments of hand hygiene’ in 2009 in an attempt to reduce the burden of health care associated infections. Many NHS trusts in England adopted this model of hand hygiene, which prompts health care workers to clean their hands at five distinct stages of caring for the patient. Our review analyses the scientific foundation for the five moments of hand hygiene and explores the evidence, as referenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 62 publications
0
40
0
3
Order By: Relevance
“…13-15 Clinical practice as seen in our study suggests that strict adherence to the WHO ‘My 5 Moments’ of HH may be infeasible in the setting of active resuscitation. Creating a set of guidelines that focuses on glove use for HH before and after patient care, after contact with body fluids and before certain clean procedures may be more effective in promoting HH compliance.…”
Section: Discussionmentioning
confidence: 84%
“…13-15 Clinical practice as seen in our study suggests that strict adherence to the WHO ‘My 5 Moments’ of HH may be infeasible in the setting of active resuscitation. Creating a set of guidelines that focuses on glove use for HH before and after patient care, after contact with body fluids and before certain clean procedures may be more effective in promoting HH compliance.…”
Section: Discussionmentioning
confidence: 84%
“…We know that the most common transmission of MRSA is from the healthcare workers' hands and clothes (Bolon ; Chou et al. ). Awareness of this fact also worried many of the participants, for example that they could carry the infection to other patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the most common route of bacterial transmission in the healthcare environment is via indirect contact with the contaminated hands of staff, but MRSA can also be spread via clothes, equipment and various other items (Chou et al. ; Morgan et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…This is also true historically across the health spectrum, ranging from the use of vitamin C to prevent scurvy (250 years before routine implementation) [28], to hand washing (100 years before routine implementation) [29], to a host of interventions and diagnostics that over treat, undertreat or mistreat patients (more than 15 years for routine implementation) [30]. …”
Section: Discussionmentioning
confidence: 99%